Intraoperative radiotherapy with low energy photons in recurrent colorectal cancer: a single centre retrospective study - Skórzewska, Magdalena; Mielko, Jerzy; Kurylcio, Andrzej; Romanek, Jarosław; Polkowski, Wojciech P. (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study: Intraoperative radiotherapy (IORT) may improve outcome of surgical treatment of recurrent colorectal cancer (CRC). The aim of this study is to determine the feasibility, safety and long-term results of surgical treatment of recurrent CRC with orthovolt IORT. Material and methods: Fifty-nine consecutive CRC patients with local recurrence (LR), undergoing surgery, were included in the retrospective analysis of prospectively collected data. The modified Wanebo classification was used to stage LR (Tr). Twenty-five (43%) patients received IORT using INTRABEAM® PRS 500. The complications were classified according to the Clavien-Dindo classification. Results: There were 32 males and 27 females, with a median age of 63 years. Multi-visceral resections were performed in 37 (63%) patients. Median hospitalization time after surgery with IORT was 7 days. One (1.7%) in-hospital postoperative death was reported. Grade 3/4 postoperative complications were found in 11 (19%) patients. Intraoperative radiotherapy had no effect on the postoperative hospitalization time, morbidity and mortality. Median survival after R0 resection was 32 months. Complete resection (R0), no synchronous liver metastases (M0), and no lateral and posterior pelvic wall involvement, were significant predictors of improved survival. Stage of LR was found to be an independent prognostic factor in the multivariate analysis (p = 0.03); Cox regression model). In patients with LR stage < Tr5, a 3-year overall survival (OS) rate was 52%. Conclusions : Combination of surgical resection and orthovolt IORT is a safe and feasible procedure that does not increase the risk of postoperative complications or prolongs the hospital stay. Despite aggressive surgery supported by IORT, the advanced stage of LR is a limiting factor of long-term survival.